Key aspects of preparing future physical education and sports specialists to provide pre-medical care - Maramukha Natalia; Tyshchenko Valeria (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
In the context of increasing demands on specialists in the field of physical culture and sports, systematic and in-depth preparation of students for providing pre-medical care is gaining particular importance. The frequency of situations requiring urgent medical intervention necessitates the improvement of educational programs to ensure a high level of professional readiness among graduates. The purpose of the research is to identify key aspects and develop criteria for the success of the educational process in forming the readiness of bachelor’s degree students in physical culture and sports to provide pre-medical care. The main definitions, such as “future bachelor of physical culture and sports” and “pre-medical care”, are clarified, and attention is focused on the need to form a methodological base and competencies necessary for effective actions in critical situations. The article is based on the works of leading scientists who have systematized key principles and pedagogical conditions for the formation of professional competencies. Special attention is paid to the analysis of scientific publications that describe the algorithms for teaching students actions in various emergency situations. The analysis of educational programs from various higher education institutions revealed a fragmented and unsystematic approach to teaching pre-medical care. The necessity of a systematic approach to preparing students, considering modern conditions, including remote and blended learning, is emphasized. The study confirms the need to form deep knowledge and practical skills in future bachelor’s of physical culture and sports to provide pre-medical care. The authors formulate readiness criteria that include cognitive, operational, and behavioral components. Key competencies and expected learning outcomes are highlighted to ensure specialists’ ability to act effectively in critical situations.